2016
DOI: 10.3892/or.2016.4742
|View full text |Cite
|
Sign up to set email alerts
|

A novel cell cycle blocker extracted from Stellera chamaejasme L. inhibits the proliferation of hepatocarcinoma cells

Abstract: Abstract. Currently, liver cancer is the sixth most prevalent cancer and the third most common cause of cancer-related death. However, effective chemotherapeutic drugs with low drug resistance and few side-effects for the clinical treatment of liver cancer are lacking. Therefore, the search for novel drugs to compensate for the defects of existing drugs is urgently needed. Herein, we successfully screened an extract named from Stellera chamaejasme L. (SCL), a historically confimed antitumor plant, through a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…ESC is widely utilized in traditional Chinese medicine and confirmed to possess antibacterial, 24 antivirus, 25 and antitumors activities. 6,7 To explore the effects of ESC on HCC progression, the authors first detected its cytotoxicity to HCC cells and found that ESC inhibited cell proliferation in a dose-and time-dependent manner, and cell sur-vival rate had a sharp downtrend at 20 lg/mL ESC. They then chose this concentration for the next experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESC is widely utilized in traditional Chinese medicine and confirmed to possess antibacterial, 24 antivirus, 25 and antitumors activities. 6,7 To explore the effects of ESC on HCC progression, the authors first detected its cytotoxicity to HCC cells and found that ESC inhibited cell proliferation in a dose-and time-dependent manner, and cell sur-vival rate had a sharp downtrend at 20 lg/mL ESC. They then chose this concentration for the next experiments.…”
Section: Discussionmentioning
confidence: 99%
“…6 Kan et al reported that ESC inhibited the proliferation of HCC cells. 7 Another article showed that ESC repressed metastasis of HCC cells. 8 However, the mechanism of ESC in modulating HCC progression is still unclear and needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), including various natural plant extracts, has shown tremendous potential for the discovery of alternative drugs for the treatment of cancer (1,2). Fewer adverse effects and cost effectiveness endow TCM great advantages over Western chemotherapeutics (3).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the efficacy of low-dose ESC was first identified in two BALB/c tumor mouse models (0.10 mg/kg or 1.00 mg/kg, which were 1/1000 or 1/100 of the doses commonly used in previous studies [5] ). In the subcutaneous xenograft tumor model, in line with our hypothesis, 0.10 mg/kg or 1.00 mg/kg ESC showed a minimal influence on the living conditions and body weight of mice compared with the negative control [Supplementary Figure 1A, http://links.lww.com/CM9/B270].…”
mentioning
confidence: 99%
“…Inspired by the in vivo results, we further explored the potential association of ESC with cell motility regulation. The commonly used dosage of ESC is 20 to 100 μg/mL in vitro [5] . In this study, we screened the safety of different ESC doses using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays, ranging from 1.56 to 25.00 μg/mL.…”
mentioning
confidence: 99%